2019
DOI: 10.1007/s10286-019-00604-0
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory- and expiratory-gated transcutaneous vagus nerve stimulation have different effects on heart rate in healthy subjects: preliminary results

Abstract: Purpose Transcutaneous auricular vagus nerve stimulation (taVNS) hasbeen considered for the treatment of sympathetically mediated disorders. However, the optimal mode of stimulation is unknown. This study aimed to compare the cardiovascular effects of respiratory-gated taVNS in healthy subjects. Methods The examination included expiratory-gated, inspiratory-gated, and non-respiratory-gated taVNS trials. Subjects were examined twice (the order of expiratory-and inspiratory-gated taVNS was changed). taVNS trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…Additionally, four studies measured vmHRV, but reported the results insufficiently to derive estimates for the meta-analysis and thus were excluded. One study had neither a sham condition nor a vmHRV baseline measurement and was thus excluded (Paleczny et al, 2021). Furthermore, we excluded two studies which did not use taVNS but transcutaneous cervical vagus nerve stimulation (Brock et al, 2017) or transcutaneous electrical nerve stimulation on cervical acupuncture points (Chan et al, 2012), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, four studies measured vmHRV, but reported the results insufficiently to derive estimates for the meta-analysis and thus were excluded. One study had neither a sham condition nor a vmHRV baseline measurement and was thus excluded (Paleczny et al, 2021). Furthermore, we excluded two studies which did not use taVNS but transcutaneous cervical vagus nerve stimulation (Brock et al, 2017) or transcutaneous electrical nerve stimulation on cervical acupuncture points (Chan et al, 2012), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Other more physiologically oriented studies have investigated the influence of tVNS on cardiac activity (Brock et al, 2017;De Couck et al, 2017;Lamb et al, 2017;Gancheva et al, 2018;Borges et al, 2019;Bretherton et al, 2019;Koenig et al, 2019;Paleczny et al, 2019;Tobaldini et al, 2019;Tran et al, 2019); autonomic outflow (Sclocco et al, 2017); sympathetic nerve activity (Clancy et al, 2014) or cardiac baroreflex sensitivity (Antonino et al, 2017); atrial fibrillation (Stavrakis et al, 2015); cardiac mechanical function (Tran et al, 2019); vagal sensory evoked potentials (Fallgatter et al, 2003(Fallgatter et al, , 2005Polak et al, 2009;Leutzow et al, 2013); persistent hiccups (Schulz-Stübner and Kehl, 2011); visual bistable perception (Keute et al, 2019a); nociceptive neuromodulation (Napadow et al, 2012;Busch et al, 2013;Laqua et al, 2014;Usichenko et al, 2017b;Janner et al, 2018); tumor necrosis factor-alpha (Brock et al, 2017); hepatic energy metabolism (Gancheva et al, 2018); whole blood culture-derived cytokines and chemokines (Lerman et al, 2016); salivary hormones (Ventura-Bort et al, 2018;Koenig et al, 2019;Warren et al, 2019); pupil diameter (Warren et al, 2019); gastroduodenal or gastrointestinal motility (Frøkjaer et al, 2016;Juel et al, 2017); muscle activity in the gastrointest...…”
Section: Acute/short-term Stimulation In Experimental Trialsmentioning
confidence: 99%
“…Additionally, four studies measured HRV, but reported the results insufficiently to derive estimates for the meta-analysis and thus were excluded. One study had neither a sham condition nor an HRV baseline measurement and was thus excluded (Paleczny et al, 2019). Furthermore, we excluded two studies which did not use taVNS but transcutaneous cervical vagus nerve stimulation (Brock et al, 2017) or transcutaneous electrical nerve stimulation on cervical acupuncture points (Chan et al, 2012), respectively.…”
Section: Resultsmentioning
confidence: 99%